2006
DOI: 10.1111/j.1529-8817.2006.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

CYTOPLASMIC MASSES PRESERVED IN EARLY HOLOCENE DIATOMS: A POSSIBLE TAPHONOMIC PROCESS AND ITS PALEO‐ECOLOGICAL IMPLICATIONS1

Abstract: In Lake Suigetsu, central Japan, greenish/lightbrown granules identified as cytoplasmic masses had been preserved in siliceous cell walls of freshwater diatoms in annual layers of lacustrine muds since the early Holocene. The lacustrine muds consisted of alternating dark-colored (rich in diatom valves, clay, and organic matter) and light-colored (mainly diatom valves) laminae. The greenish/lightbrown granules were predominately preserved in frustules of the genus Aulacoseira preserved in the dark-colored lamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Nonetheless, it is impossible to equate robust chloroplasts with a living cell without culturing individual cells (Stockner and Lund 1970), which I did not do in this study. However, in cases where the preservation of cytoplasmic structures in the fossil record is exceptional—often as a result of modern displacement along the sedimentary column due to invertebrate burrowing activity (Stockner and Lund 1970)—the chloroplast are usually condensed (Wolfe et al 2006; Tanimura et al 2006). Moreover, good agreement between chloroplast-bearing cell counts and cultures in some freshwater lakes indicated that at least in these lakes the chloroplast counts are a realistic measure of algal viability in recent sediments (Stockner and Lund 1970).…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, it is impossible to equate robust chloroplasts with a living cell without culturing individual cells (Stockner and Lund 1970), which I did not do in this study. However, in cases where the preservation of cytoplasmic structures in the fossil record is exceptional—often as a result of modern displacement along the sedimentary column due to invertebrate burrowing activity (Stockner and Lund 1970)—the chloroplast are usually condensed (Wolfe et al 2006; Tanimura et al 2006). Moreover, good agreement between chloroplast-bearing cell counts and cultures in some freshwater lakes indicated that at least in these lakes the chloroplast counts are a realistic measure of algal viability in recent sediments (Stockner and Lund 1970).…”
Section: Methodsmentioning
confidence: 99%
“…However, we rarely observe deep holes in frustules with the exception of Aulacoseira sp. 25 Chaetoceros is one of the most species-rich genera of diatoms in the marine phytoplankton [26][27][28][29] . The cells of Chaetoceros forming chains have long setae protruding from each of their four corners 30,31 .…”
Section: Introductionmentioning
confidence: 99%